SOCIAL CONSEQUENCES OF MODERN RELIGIOUS TERRORISM - N. Grigoriev; E. Rodyukov (Вестник университета, 2016)
The attempt of analysis of modern religious terrorism is undertaken in the article. Religious assassinations take place everywhere in the conditions of the aspiring to globalization world and affect all spheres of life of society. Religious terrorism - one of the most early in human history directions of terrorism, that already during very great while is used in opposing different by the nature and organizations of socio-political forces, including religiously-fanatic groupments of different scale and orientation, political and ethnic elites, social and political associations, separate states. Religious terrorism today it, foremost, crime against humanity.